Long-term outcome of anorexia nervosa in a prospective 21-year follow-up study - Löwe, Bernd; Zipfel, Stephan; Buchholz, Christine; Dupont, Yvonne; Reas, Deborah Lynn; Herzog, Wolfgang (Psychological medicine, 2001)
Given our poor understanding of the very long-term course of anorexia nervosa, many questions remain regarding the potential for recovery and relapse. The purpose of the present study was to investigate long-term outcome and prognosis in an anorexic sample 21 years after the initial treatment.